Instrumental and sensory techniques to characterize the texture of foods suitable for dysphagic people: A systematic review. Issue 3 (27th April 2022) - Ibañez, Francisco C.; Merino, Gorka; Marín‐Arroyo, María Remedios; Beriain, María José
Abstract: The interest to characterize texture‐modified foods (TMFs) intended for people with oropharyngeal dysphagia (OD) has grown significantly since 2011. Several instrumental and sensory techniques have been applied in the analysis of these foods. The objective of the present systematic review was to identify the most appropriate techniques, especially for the food industry and clinical setting. The search was carried out in three online databases according to the "Preferred Reporting Items for Systematic Reviews and Meta‐Analyses" (PRISMA). Across the multiple trials reviewed, Texture Profile Analysis and the Uniaxial Compression Test were most used as the instrumental technique for solid foods, and the Back Extrusion Test for fluid and semisolid foods. All trials used descriptive analysis as the sensory technique. However, the experimental conditions of the trials lacked standardization. Consequently, the results of the trials were not comparable. To properly characterize the texture of TMFs intended for OD by each technique, an international consensus is needed to establish standardized experimental conditions. Methods based on these techniques should also be validated by collaborative studies to verify repeatability, replicability, and reproducibility.